2017
DOI: 10.1016/j.celrep.2017.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 Is Expressed on Lymphoid Tissue Residing LTi-like Group 3 Innate Lymphoid Cells and Associated with Ectopic Lymphoid Aggregates

Abstract: SummaryHere, we characterize a subset of ILC3s that express Neuropilin1 (NRP1) and are present in lymphoid tissues, but not in the peripheral blood or skin. NRP1+ group 3 innate lymphoid cells (ILC3s) display in vitro lymphoid tissue inducer (LTi) activity. In agreement with this, NRP1+ ILC3s are mainly located in proximity to high endothelial venules (HEVs) and express cell surface molecules involved in lymphocyte migration in secondary lymphoid tissues via HEVs. NRP1 was also expressed on mouse fetal LTi cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 49 publications
10
116
1
Order By: Relevance
“…Of note, many markers are expressed differentially among each ILC group. For instance, CD39, CD56, NKp46 or CD161 are expressed heterogeneously by human ILC3 . Similar observations have been carried out for ILC2 cells and expression of NKp30, CD49a or c‐Kit .…”
Section: Ilc Subset Heterogeneity In Humanssupporting
confidence: 79%
See 1 more Smart Citation
“…Of note, many markers are expressed differentially among each ILC group. For instance, CD39, CD56, NKp46 or CD161 are expressed heterogeneously by human ILC3 . Similar observations have been carried out for ILC2 cells and expression of NKp30, CD49a or c‐Kit .…”
Section: Ilc Subset Heterogeneity In Humanssupporting
confidence: 79%
“…Of note, NKp44 + ILC3 can be divided into two populations based on the expression of neuropilin‐1 (NRP‐1). NRP‐1 + ILC3 produces more cytokines than NRP‐1 − ILC3, and is detected only in lymphoid tissues and inflamed lung tissue …”
Section: Ilc Subset Heterogeneity In Humansmentioning
confidence: 99%
“…In humans, it has been difficult to identify a distinct LTI population. However, a recent report showed that ILC3 expressing neurophilin 1 (NRP1) are predominantly found near high endothelial venules in lymphoid but not mucosal tissues [51]. NRP1 + ILC3 induce ICAM-1 and VCAM-1 expression on mesenchymal stromal cells, indicative of LTI function.…”
Section: Ilc3mentioning
confidence: 99%
“…NRP1 + ILC3 induce ICAM-1 and VCAM-1 expression on mesenchymal stromal cells, indicative of LTI function. As in the mouse, human NRP1 + ILC3 produce significant levels of IL-22 and IL-17A [51]. Hence, these cells might represent the human LTI.…”
Section: Ilc3mentioning
confidence: 99%
“…56 Recently, ILC3s were detected in inflammatory aggregates and near blood vessels in lungs of smokers and COPD patients providing insight into the initiation of smoke-induced ectopic pulmonary lymphoid aggregates ( Figure 1). 15 …”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%